Parents' experiences of using a hybrid closed-loop system (CamAPS FX) to care for a very young child with type 1 diabetes: Qualitative study. (May 2022) - Kimbell, Barbara; Rankin, David; Hart, Ruth I.; Allen, Janet M.; Boughton, Charlotte K.; Campbell, Fiona; Fröhlich-Reiterer, Elke; Hofer, Sabine E.; Kapellen, Thomas M.; Rami-Merhar, Birgit; Schierloh, Ulrike; Thankamony, Ajay; et al.
Highlights: First qualitative study of closed-loop system use among parents of young children. System use can facilitate greater normality for the child, parents and siblings. Parents using this technology may need less health professional support. Closed-loop systems may need to be customised for very young children. Abstract: Aims: To explore parents' experiences of using a hybrid closed-loop system (CamAPS FX) when caring for a very young child (aged 1–7 years) with type 1 diabetes. Methods: Interviews with n = 33 parents of 30 children who used the system during a randomised controlled trial. Data analysis used a descriptive thematic approach. Results: While some parents were initially reticent about handing control to the system, all reported clinical benefits to using the technology, having to do less diabetes-related work and needing less clinical input over time. Parents welcomed opportunities to enhance the system's efficacy (using Ease-off and Boost functions) as required. Parents described how the system's automated glucose control facilitated more normality, including sleeping better, worrying less about their child, and feeling more confident and able to outsource care. Parents also described more normality for the child (alongside better sleep, mood and concentration, and lessened distress) and siblings. Parents liked being able to administer insulin using a smartphone, but suggested refinements to device size and functionality. Conclusions: Using a hybrid closed-loop system in very young children can facilitate greater normality and may result in a lessened demand for health professionals' input. Systems may need to be customised for very young children.